2007
DOI: 10.1103/physrevd.76.034506
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structure of the quenched QCD vacuum with overlap fermions

Abstract: Overlap fermions have an exact chiral symmetry on the lattice and are thus an appropriate tool for investigating the chiral and topological structure of the QCD vacuum. We study various chiral and topological aspects of quenched gauge field configurations. This includes the localization and chiral properties of the eigenmodes, the local structure of the ultraviolet filtered field strength tensor, as well as the structure of topological charge fluctuations. We conclude that the vacuum has a multifractal structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
129
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 89 publications
(141 reference statements)
11
129
0
Order By: Relevance
“…A similar structure has been also observed in QCD by a different group [57] and also in two dimensional CP N −1 model [66]. Furthermore, the studies of localization properties of Dirac eigenmodes have also shown evidence for the delocalization of low-lying modes on effectively low-dimensional surfaces.…”
Section: B Insights From Numerical Lattice Simulations and Holographmentioning
confidence: 50%
See 4 more Smart Citations
“…A similar structure has been also observed in QCD by a different group [57] and also in two dimensional CP N −1 model [66]. Furthermore, the studies of localization properties of Dirac eigenmodes have also shown evidence for the delocalization of low-lying modes on effectively low-dimensional surfaces.…”
Section: B Insights From Numerical Lattice Simulations and Holographmentioning
confidence: 50%
“…It is important to emphasize that the singular behaviour of the contact term ∼ δ 4 (x) is not an artifact of any approximations, in spite of the fact that this behaviour was established in simplified models: in the "deformed QCD" [46] and in the Veneziano model (19). This singular behaviour and the vanishing width (in continuum limit) of the contact term have been observed in the lattice simulations [56][57][58][59][60].…”
Section: B Insights From Numerical Lattice Simulations and Holographmentioning
confidence: 96%
See 3 more Smart Citations